Campus tecnológico y universitario de la Orinoquia - Calderón Medina, Jazmín (Universidad Antonio Nariño, 2021)
The departament of Arauca currently has a deficit in Higher Education coverage. According to DANE statistics, coverage for 2018 is only 8.8%. This is a worrying figure, since every day fewer young people are willing and table to access an HEI (Higher Education Institution), this hinders the training of professionals who promote the social and economic sector of the departament of Arauca.